Does Digital Awareness Reduce Misreporting of Covid-19 Data? An Empirical Investigation - Youkta, Kumari; Paramanik, Rajendra Narayan; Nupur, Shreya (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2023)
Manipulation of pandemic induced casualty data poses serious threat to globe. This study is an empirical attempt to assess possible factors causing such data fudging. In order to investigate strategic data misreporting by countries, we have employed acclaimed Benford’s law on numbers of deaths reported by 129 countries during both waves of pandemic. Finding reveals that alongside factors like degree of democracy, transparency etc., countries with poor digital awareness are subject to greater manipulation of data.